HASIL TUMPANG SARI HUTAN TERHADAP PENDAPATAN PESANGGEM DAN BIDANG DASAR TANAMAN POKOK DI CEPU, BLORA - Akub J Abdurachman; Suwidji Basuki (Jurnal Penelitian Hasil Hutan, 1988)
The  scarcity  of  agriculture  land and  the  increasing population around  the  forest  have aucsed pressure on  the forest resource.   Taungya  system  approach   is aimed  at  improving   the prosperity   of  the people  surrounding   the  forest  through tree planting  coupled   with  crops in  two  years period.The result of observation on Taungya system in Pasar Sore Forest District  Administrations, Cepu,  Central Java, revealed  that  the  present  income  from taungya  system   contributed   about  22  % of  total  income.  Other  interesting   result showed   that  soil fertilization   by peasant,   beside gives positive   effect on peasant  income,   it also causes positive  impact  on the  growth   of  trees  basal areas.  Some   variables analyzed   in  this study  are  taungya  income   (Y1),  the  cost of  production facility  such  as fertilizer  and  insectiside  cost  (X1) man power   (X2), non-taungya income   (X3),  and  basal growth   (Y2). The  relationship   resulted  in regression  models  as follows  : Y1  =   -32,23 + 14,04X1  +   0,23X2  -  0,04X3  (R2 = 0,83) Y2  =   2.009,45 + 326,09  X1 + 2,98  X2  - 1,29  X3  (R2 = 0,78)